A abordagem por competência nos currículos de formação profissional técnica na área de saúde - Canuto, Ondina Maria Chagas (2012)
The main aim of this study was to investigate, through a case study, the presence and influence of the approach by curriculum competence construction, organization and development in technical formation in the health area, through the activities of the Public Health School of the State of Ceará. The Education Guidelines and Bases (LDB), instituted by Law 9.394/96 represented a landmark for professional education policy, followed by a series of decrees, resolutions, opinions, ordinances and public policies that will be regulating and shaping the aforesaid policy. The technical training in health, starting from the official guidance has (re)designated curricula based on skills and national curriculum guidelines for vocational technical level. This process required a new dynamics in order to change the curriculum and teaching practices. The field of technical training in health was and is oriented by the emergence of the Unified Health System - SUS (Law 8.080/90), public policy which has required, since the 90s, new processes of qualification for the workers. Therefore, it was issued the need to rethink the curricula of vocational training which oppose a traditional model, in order to respond to emerging demands of the SUS. The National Curriculum Benchmarks of Professional Education for the Technical Health Area, established in 2000, started orienting this curriculum construction. We start from the understanding of curriculum as a formal instrument that guides the path of formation of students including their learning and experiences that are planned, conducted and evaluated by the school. From the method of content analysis it was conducted document analysis, interviews and field observations, enabling the understanding of the approach by competences in the curricula of technical training in the health area. The curriculum re-design constructed by the training institutions departing from the requirements of the formation for competence, which is object of this study, found out in the public health sector in Brazil, a critical, but open field, pointing to the curriculum development as a social construction comprising the competencies from a complex know how to act. The survey results allowed us to confirm our hypothesis, identifying that the ESP-CE, from the official guidelines, advertises and draws its curricula based on the competence approach, but whether in written, expressed by the subjects involved in research or in the observations, there is an epistemological stance consistent with this approach, which highlights the fragility of this systematic approach to the construction, organization and curriculum development. Thus, the construction of curricula for training in technical skills at the Public Health School in Ceará remains a challenge, so as to convert the curriculum competencies in a guiding instrument for the formative processes that keeping theoretical and methodological coherence between planning, implementation and evaluation of training processes, strengthen the harmony between the world of training and the workplace, responding to the demands of training to qualify the professional practices of workers and the Unified Health System.